Ankle Injuries in the Pediatric Athlete. Issue 4 (December 2016) - Erickson, John B.; Samora, Walter P.; Klingele, Kevin E.
Abstract : Foot and ankle injuries are the second most common reason for young athletes to present to a primary care physician, and account for up to 30% of visits to sports medicine clinics in this population. Heightened performance expectations placed on today's young athletes have led to intense training and competition demands. With increasing rates of sport participation among children and adolescents, it is important for treating physicians to have an understanding of the evaluation and management of ankle injuries seen in the pediatric athlete. In treating young athletes it is important to keep in mind the unique developmental and anatomic differences between the skeletally mature and skeletally immature ankle. These differences predispose young athletes to unique injuries not seen in adults. These include injuries that result from congenital or developmental variations, acute injuries, and overuse type injuries.